Role of Prognostic Factors in Success of Intrauterine Insemination (IUI) Procedure (Medical Forum Monthly, 2024)
Objective: To confirm-cum-identify important prognostic factors to improve outcome and provide a model to centers with lower success rates and newly developed centers.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Center for Reproductive Medicine, Rehman Medical Institute, Peshawar from January 2015 to January 2017.Materials and Methods: One hundred and thirteen patients who were eligible for the inclusion criteria were included. In this study controlled ovarian stimulation was started giving HMG injections to patients following follicular tracking accordingly to get required size and number of follicles. After administration of IVF-C 10,000 IU twice insemination was performed at 36 and 44 hours with 0.5 ml volume of prepared semen sample via gradient or swim-up method.Results: We found that >2 follicles was a fruitful prognostic factor (value 0.02) than 1-2 follicles. The semen preparation in culturing media produced better percentile 29.03% as compared to sperm wash media 12.19% in positive and negative case. While preparing semen sample through gradient method we got 28.57 % positive result as compared to swim-up method (P value 0.06). During this research we found that our pregnancy rate was 16.81 % pregnancies with take home baby rate of 63.15%.Conclusion: In treating infertile couple, prognostic factors play a key role in improving IUI success rate